Cerebral dominance associated with the labour performance of teachers in a UGEL of Lima - Torres Valladares, Manuel (2009)
The progresses in neurosciences of the education put into spotlight the great importance that the human brain has to develop in order to obtain its full operation and make it highly productive. This development of the brain must start in the family and continued actively in the school as one of the main task and the responsible of this work is the teacher that is why the development of investigations and the creation of programmes that capacitate the teacher are task that cannot be postponed. The main purpose of this study is to identify the predominant cerebral quadrants and the characteristics of the labour development in a sample of teachers from Lima’s UGEL, and correlate them later. The instruments utilised were: the Inventory of Cerebral Dominance of Ruiz-Bolívar and collaborators and the questionnaire of self-report of teacher’s labour development of Fernández Arata. These instruments were taken into the respective analysis that showed the tests are valid and trustable. The sample were constituted by 251 teachers of Lima’s UGEL, from whom 118 were men and 133 women, to whom the indicated questionnaires were taken and they were later correlated. The results show that significant and positive correlations exist between the Cere bral dominance and the labour development of teacher. It was also found that a high percentage of teachers that do not have defined cerebral dominance and that in general, the limbic brain predominate in the teachers, especially the cerebral quadrant B, the one destined to fulfil programmes previously planned without moods changes.